1974
DOI: 10.1128/iai.10.1.6-10.1974
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Temperature-Dependent Inactivating Factor of the Thermostable Direct Hemolysin in Vibrio parahaemolyticus

Abstract: A factor was found in Vibrio parahaemolyticus which inactivated the hemolytic activity of a purified, thermostable direct hemolysin. The inactivating factor was associated with the hemolysin but could be separated from it by diethylaminoethyl-cellulose column chromatography. The inactivating factor was activated by heating at 50 to 60 C, but was itself thermolabile and lost activity on heating to 70 to 100 C. The mechanism of the Arrhenius effect, observed with crude hemolysin of V. parahaemolyticus, is as fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 2 publications
3
20
0
Order By: Relevance
“…The remarkable heat stability of the Kanagawa hemolysin has been reported previously (Miwatani et al, 1972;Sakurai et al, 1973;Takeda et al, 1974). Our study indicates that heat inactivation rates of this stable hemolysin in buffer, crustacea and shellfish homogenates are linear functions and thus differ sharply from the curvilinear thermal-destruction-rate plots that we obtained for Clostridium sp.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The remarkable heat stability of the Kanagawa hemolysin has been reported previously (Miwatani et al, 1972;Sakurai et al, 1973;Takeda et al, 1974). Our study indicates that heat inactivation rates of this stable hemolysin in buffer, crustacea and shellfish homogenates are linear functions and thus differ sharply from the curvilinear thermal-destruction-rate plots that we obtained for Clostridium sp.…”
Section: Resultssupporting
confidence: 69%
“…Limited investigations of the time-temperature relationship of Kanagawa hemolysin inactivation were conducted by Miwatani et al (1972) and Takeda et al (1974). Sakurai et al (1973) reported that purified hemolysin in phosphate buffer (pH 7.0) was not inactivated by heating at 100°C for 10 min.…”
Section: Hemolysin Productionmentioning
confidence: 99%
“…The purified preparation of thermostable direct hemolysin contained a single protein with a molecular weight of about 42,000 (7).Assay of hemolytic activity. Hemolytic activity was assayed as described previously (7,13). The standard reaction mixture (2.5 ml) contained 10 mM tris(hydroxymethyl)aminomethane (Tris) -hydrochloride buffer (pH 7.2), 10 mM CaCl12, 0.9% NaCl, the thermostable direct hemolysin, and 1.25 ml of a 1% suspension of human erythrocytes (about 8.3 x 107 cells/ml).…”
mentioning
confidence: 99%
“…However, hepatic phosphorylase activity in the poisoned mice was appreciably higher than that in control mice after 2 hr, whereas its activity after 18 hr was not significantly different from that in the control fasted mice (37). Another study (41) in our laboratory has shown that in mice injected intraperitoneally with live Vibrio parahaemolyticus (pathogenic strain), the hepatic phosphorylase and G-6-Pase activities showed a tendency similar to the rise and fall in the blood sugar level although the pathogen exacerbated a heat-stable hemolytic toxin (47) showing lethality to mice, in addition to endotoxin.…”
Section: Discussionmentioning
confidence: 71%